Explaining different orientations to the 2013 Gezi Park demonstrations in Istanbul, Turkey. (11th February 2019) - Stewart, Andrew L.; Leach, Colin Wayne; Bilali, Rezarta; Çelik, Ayşe Betül; Cidam, Atilla
Abstract : Although a notable minority orient to real‐world demonstrations by actively participating, other less involved, safer, orientations are more frequent. Thus, in the context of anti‐government demonstrations in Gezi Park/Taksim Square in Istanbul, Turkey, in 2013, we distinguished between the orientations of participating, visiting, and watching. Study 1 ( N  =   359) and Study 2 ( N  =   327) confirmed that participating was characterized by greater experience of police violence and feelings of collective empowerment (Drury & Reicher, European Journal of Social Psychology, 35, 2005, 35) than visiting and watching the demonstrations. Expanding upon and replicating the findings from Study 1, Study 2 examined identification with protestors and left‐wing ideology, along with constructs (social support, anger at the government, protestor's efficacy, endorsement of protestors) from the dynamic dual pathway model (van Zomeren et al ., Personality and Social Psychology Review, 16, 2012, 180) as predictors of the three different orientations to the demonstrations. As expected, the dynamic dual pathway model predicted reported participation via endorsement of protestors, independent of identification with protestors and left‐wing ideology.